An acute case of intoxication with cyanobacteria and cyanotoxins in recreational water in Salto Grande Dam, Argentina - Giannuzzi, Leda (2011)
Cyanobacterial blooms and hepatotoxic microcystins (MCs) usually occur in summer, constituting a sanitary and environmental problem in Salto Grande Dam, Argentina. Water sports and recreational activities take place in summer in this lake. We reported an acute case of cyanobacterial poisoning in Salto Grande dam, Argentina, which occurred in January 2007. Accidentally, a young man was immersed in an intense bloom of Microcystis spp. A level of 48.6 μg·L -1 of microcystin-LR was detected in water samples. Four hours after exposure, the patient showed nausea, abdominal pain and fever. Three days later, dyspnea and respiratory distress were reported. The patient was hospitalized in intensive care and diagnosed with an atypical pneumonia. Finally, a week after the exposure, the patient developed a hepatotoxicosis with a significant increase of hepatic damage biomarkers (ALT, AST and γGT). Complete recovery took place within 20 days. This is the first study to show an acute intoxication with microcystin-producing cyanobacteria blooms in recreational water.